Pre-Service Turkish and Classroom Teachers’ Views on Root Values - Erhan Çapoğlu (Sakarya University Journal of Education)
Values are the building blocks of a society; they create societies and contain their characteristics. Accordingly, the teaching of values is very important for a society. The role of teachers in the teaching of values is large. In the 2019 curriculum for Turkish language classes, such values are also referred to as ten root values. Therefore, it is necessary for teachers and pre-service teachers to know the ten root values in the Turkish language teaching programme in terms of teaching values. In this study, the views of pre-service Turkish teachers and pre-service classroom teachers on root values were analysed. The study group consisted of a total of 60 pre-service teachers from Turkish education (30) and classroom education (30) programmes who were studying at a public university in the second semester of the 2021-2022 academic year. A semi-structured interview form consisting of five open-ended questions was administered to these pre-service teachers and the obtained data were analysed with content analysis. When the results of the research were evaluated, it was concluded that pre-service Turkish and classroom education teachers considered values to be basic elements. Pre-service teachers described the role of values in education as supportive, while pre-service Turkish teachers also described the concept as necessary and pre-service classroom teachers described it as a way of raising useful individuals. It was concluded that both groups viewed root values as the values people should have, and the values they viewed as priorities were love and justice. Both groups suggested that empathy be added to the root values. Despite some differences, Turkish and classroom education pre-service teachers generally shared the same views on values and root values.